MEDICAL TREATMENT OF HEPATOCELLULAR CARCINOMA - Alessandro Granito; Luigi Bolondi (Mediterranean Journal of Hematology and Infectious Diseases)
Hepatocellular carcinoma (HCC) is the fifth most common neoplasm and the third leading cause of cancer-related deaths worldwide. Cirrhosis, most often due to viral hepatitis, is the predominant risk factors for HCC and geographical differences in both risk factors and incidence are largely due to epidemiological variations in hepatitis B and C infection. Hepatic function is a relevant parameter in selecting therapy in HCC. The current clinical classification of HCC split patients into 5 stages, with a specific treatment schedule for any stage. As patients with early stages can receive curative treatments, such as surgical resection, liver transplantation or local ablation, surveillance program in high-risk populations has become mandatory. Sorafenib, a multikinase inhibitor, has recently shown survival benefits in patients at advanced stage of disease. Hopefully, new molecular targeted therapies and their combination with sorafenib or interventional and surgical procedures, should expand the therapeutic armamentarium against HCC.